The world will never see the like the Gettysburg reunion of 1913 - Hopkins, John L. 1957- (Savas Beatie, 2024)
"This is the story of the largest reunion of Union and Confederate veterans ever held: its genesis and planning, the obstacles overcome on the way to making it a reality, its place in the larger narrative of sectional reunion and reconciliation, and the individual stories of the veterans who attended."
Keywords: Geschcihte 1913; Schlacht von Gettysburg; Zusammenkunft; Veteran; Gettysburg Reunion, 1913; Gettysburg, Battle of, Gettysburg, Pa., 1863; Bataille de Gettysburg, Gettysburg, Penns., 1863; Pennsylvania / Gettysburg / https://id.oclc.org/worldcat/entity/E39PBJyGR8Wky4JPyC9gmJTJXd; Gettysburg (Pa.), Battle of, 1863; 1863-1913